Linear Atrophoderma of Moulin: A Distinct Entity?. Issue 3 (9th October 2012) - de, Emily; Echols, Kathryn; Pearl, Henna; Davis, Loretta
Abstract Linear atrophoderma of Moulin (LAM) is a rare dermatologic disorder characterized by a hyperpigmented atrophoderma that consistently follows the lines of Blaschko. There are many clinical and histologic similarities between LAM, atrophoderma of Pasini and Pierini (APP), and morphea, and whether LAM represents part of a disease spectrum or its own distinct entity is debated. This case of a 16‐year‐old boy with LAM supports the hypothesis that LAM, APP, and morphea are a spectrum of disorders rather than unique entities. Although the patient's overall clinical picture supports a diagnosis of LAM with hyperpigmented, depressed lesions following the lines of Blaschko and perivascular lymphocytic infiltrate on biopsy, the bilateral presentation typical of APP, collagen entrapment of eccrine ducts typical of morphea, and changes in dermal collagen illustrate features spanning all three disorders, suggesting a relationship between these conditions that represents a spectrum of disease. Furthermore, a review of all reported cases of LAM in the literature suggests an evolving definition beyond what Moulin and colleagues originally described, including features related to those of APP and morphea.